PEMANFAATAN TEKNOLOGI BERBASIS ANDROID SEBAGAI MEDIA BELAJAR MATEMATIKA ANAK SEKOLAH DASAR - Ependi, Usman; Sopiah, Nyimas (Universitas Bina Darma, 2015)
Mobile (HP) is a tool used by many people in Indonesia, to communicate and seek information. HP is not only used by teenagers and adults, but also can be used by children. Children who use mobile phones are only used for pleasure, such as playing games, which only can be downloaded at HP. Elementary school students (elementary) class VI is the final level students who will face the National Examination (UN). Subjects of Mathematics is one of the subjects that are not so popular. To anticipate gnats students not only play at HP but also can learn, it will be made application of the measurement is one of the materials on the subjects of Mathematics. Applications created using the Android operating system. System development method used is the Wireless Software Engineering.